2004
DOI: 10.1007/s00170-004-1865-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapid investment casting: direct and indirect approaches via model maker II

Abstract: Although investment casting (IC) provides an economical method for the mass production of metal parts with complex and intricate features, the relatively long lead times and high tooling costs involved in the manufacture of metal moulds for the fabrication of sacrificial IC wax patterns lead to cost justification problems for customised single casting, small and medium quantity production. The application of rapid prototyping (RP) technologies to fabricate complex sacrificial IC patterns can result in signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 3 publications
0
55
0
Order By: Relevance
“…Additive manufacturing (AM) can be defined as a group of techniques to obtain final parts, prototypes, cores, injection molds for plastics, electrodes for erosion, etc., in a short period of time from a 3D file elaborated with CAD software [1,2]. As a result of these processes, it is possible to carry out, in a relatively short period of time, different specimens and geometries to validate the definitive design, and to undertake the serial production with reduced development times, and with lower development costs.…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing (AM) can be defined as a group of techniques to obtain final parts, prototypes, cores, injection molds for plastics, electrodes for erosion, etc., in a short period of time from a 3D file elaborated with CAD software [1,2]. As a result of these processes, it is possible to carry out, in a relatively short period of time, different specimens and geometries to validate the definitive design, and to undertake the serial production with reduced development times, and with lower development costs.…”
Section: Introductionmentioning
confidence: 99%
“…It was found to be very useful in that it enables elimination of feeding system designs that are obviously useless as well as focus on promising values of casting parameters. Among all papers, mainly case studies, that were found in literature dealing with rapid casting of parts based on an original to be replicated [1,2,[5][6][7]11,13,16,17,19,25,26,29], all but three tacitly admit that a right-first-time casting can be achieved, obviously by selecting casting feeding and process parameters according to experience. The three exceptions [16,19,29] used simulation to check that the single envisaged casting system design was suitable, i.e., without trying out alternatives.…”
Section: Virtual Castingmentioning
confidence: 99%
“…In addition, even if the layer thickness is small enough, the resulting fabrication time may be prohibitively large, especially for large parts [7].…”
mentioning
confidence: 99%
“…The perception of RP to be implemented as sacrificial master pattern in Investment Casting (IC) was dated back in 1989 [1]. Initially, the block mould was used in IC, and the concept is to build the RP parts that required no additional finishing.…”
Section: Introductionmentioning
confidence: 99%